Optimizing The Use of Social Media as A Public Communication Tool For The Badung Regency Government During The Pandemic - Putu Nomy Yashinta; Bimo Dwi Nur Romadhon Sukadi; Ni Putu Mirna Sari (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2023)
Public communication is a form of communication used to effectively and efficiently communicate the message to the public through the media or in person. Governance, including public communications management, is also tailored to the development of information technology. The Communications and Informatics Office (Diskominfo) Badung Regency using a variety of social media, it has to pass on information from the public. This study aims to reveal the general overview of public communication that is done, the stages in the delivery of public information, and opportunities as well as challenges in the management of public communication by Diskominfo Badung Regency. The research method used in this study is mixed methods. The results of this study stated that public Communication is built by Diskominfo Badung Regency, through social media that they had in the times of the pandemic Covid-19 is fairly optimal range of the percentage of 60-70%. However, there are still areas for improvement to address opportunities and challenges.